A macro assessment of China effects on Malaysian exports and trade balances. Issue 1 (2014) - ,; ,; ,
<x xml:space="preserve">Abstract</x> Purpose – This paper aims to focus on the impact of China's export expansion on Malaysian monthly trading with to her 12 major trading partners over the liberalization era. Design/methodology/approach – The analytical framework comprises of both the export and trade balance models. Unit root and cointegration tests with break and error correction modeling are employed in the analyses. Findings – Regime shifts are evident in the long run where structural break(s) found mostly coincides with the Asia crisis and China's accession into WTO. While the income effects are more apparent in most cases, the real exchanges are rather insignificant and incorrectly signed for Malaysian bilateral trading. Besides, the trade balance estimation is generally more consistent that the Chinese exports have exhibited complementary effects in the long‐run, mainly for advanced export destination such as Australia, Germany, Japan, the UK and the USA. On the whole, there is insufficient evidence to support the "PRC competitive threat". Practical implications – The empirical evidence disfavors currency devaluation for current account correction and reveals that the fear for China effect might be over‐projected. Closer regional collaboration and trade integration between the two nations are well expected. Originality/value – The paper assesses the China's crowding out effect and magnitudes of Malaysian export and trade balance elasticities with model specifications that consider structural breaks. The paper also assesses the macro dimension of income and real exchanges effects.